Update on the diagnosis and management of early rheumatoid arthritis - Taylor, P (Royal College of Physicians, 2020)
The clinical spectrum of rheumatoid arthritis (RA) presentation is heterogeneous, with wide variation in age of onset, degree of joint involvement and severity. Delayed rheumatological referral is associated with less favourable long-term outcomes. Multidisciplinary teamwork is key to the success of a holistic approach to patient care and addressing issues that are important to the person. Pharmacological treatment of early RA aims to optimally suppress the inflammatory component of the disease with an ideal treatment target of remission. The overarching aim of management of early RA is to achieve a quality of life that permits the individual to pursue normal work, domestic and social activity.